Optic Neuritis, Abnormal MRI and Outcome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2011)
Researchers at Birmingham Children's Hospital, and Great Ormond Street and Evelina Children's Hospitals, London, UK followed 44 children (female/male ratio 1.8; median age 10.9 years) with a first-episode optic neuritis for a median of 1 year (mean, 1 year 10 months).